Risk of Late Relapse or Reinfection With Hepatitis C Virus After Achieving a Sustained Virological Response: A Systematic Review and Meta-analysis - Bryony Simmons; Jawaad Saleem; Andrew Hill; Richard D Riley; Graham Cooke (2016)
Background. Treatment for hepatitis C virus (HCV) can lead to sustained virological response (SVR) in over 90% of people. Subsequent recurrence of HCV, either from late relapse or reinfection, reverses the beneficial effects of SVR. Methods. A search identified studies analysing HCV recurrence post-SVR. The recurrence rate for each study was calculated using events/person years of follow-up (PYFU). Results were pooled using a random-effects model and used to calculate 5-year recurrence risk. Three patient groups were analysed: (1) Mono-HCV infected “low-risk” patients; (2) Mono-HCV infected “high-risk” patients (injecting drug users or prisoners); (3) human immunodeficiency virus (HIV)/HCV coinfected patients. Recurrence was defined as confirmed HCV RNA detectability post-SVR. Results. In the 43 studies of HCV mono-infected “low-risk” patients (n = 7969) the pooled recurrence rate was 1.85/1000 PYFU (95% confidence interval [CI], .71–3.35; I2 = 73%) leading to a summary 5-year recurrence risk of 0.95% (95% CI, .35%–1.69%). For the 14 studies of HCV monoinfected “high-risk” patients (n = 771) the pooled recurrence rate was 22.32/1000 PYFU (95% CI, 13.07–33.46; I2 = 27%) leading to a summary 5-year risk of 10.67% (95% CI, 6.38%–15.66%). For the 4 studies of HIV/HCV coinfected patients the pooled recurrence rate was 32.02/1000 PYFU (95% CI, .00–123.49; I2 = 96%) leading to a summary 5-year risk of 15.02% (95% CI, .00%–48.26%). The higher pooled estimates of recurrence in the high-risk and coinfected cohorts were driven by an increase in reinfection rather than late relapse. Conclusions. SVR appears durable in the majority of patients at 5 years post-treatment. The large difference in 5 year event rate by risk group is driven mainly by an increased reinfection risk.